2017
DOI: 10.1021/acssynbio.6b00388
|View full text |Cite
|
Sign up to set email alerts
|

Genome Engineering of Virulent Lactococcal Phages Using CRISPR-Cas9

Abstract: Phages are biological entities found in every ecosystem. Although much has been learned about them in past decades, significant knowledge gaps remain. Manipulating virulent phage genomes is challenging. To date, no efficient gene-editing tools exist for engineering virulent lactococcal phages. Lactococcus lactis is a bacterium extensively used as a starter culture in various milk fermentation processes, and its phage sensitivity poses a constant risk to the cheese industry. The lactococcal phage p2 is one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 41 publications
1
74
0
Order By: Relevance
“…The appearance of CEMs was observed at varying frequencies when Types I and II CRISPR-Cas systems were used to edit phages. 2730 In contrast, neither a PAM nor a seed sequence has been identified for CRISPR-Cas10. 40,45 This system is also extremely tolerant to mismatches between the crRNA and protospacer during antiphage immunity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The appearance of CEMs was observed at varying frequencies when Types I and II CRISPR-Cas systems were used to edit phages. 2730 In contrast, neither a PAM nor a seed sequence has been identified for CRISPR-Cas10. 40,45 This system is also extremely tolerant to mismatches between the crRNA and protospacer during antiphage immunity.…”
Section: Resultsmentioning
confidence: 99%
“…26 However, recent reports have shown that CRISPR-Cas (Clustered regularly-interspaced short palindromic repeats-CRISPR-associated) systems in distinct bacteria can facilitate phage editing. 2730 CRISPR-Cas systems are a diverse class of prokaryotic immune systems that use small CRISPR RNAs (crRNAs) and Cas nucleases to detect and destroy phages and other nucleic acid invaders. 3136 In these systems, CRISPR loci maintain an archive of short (30–40 nucleotide) invader-derived sequences called “spacers” integrated between similarly sized DNA repeats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of phages have been modified with type II CRISPR systems; including phage 2972 infecting Streptococcus thermophiles, phage P2 infecting Lactococcus. lactis, phiKpS2 infecting Klebsiella pneumoniae and phages T2, T4, T7 and KF1 that infect E. coli respectively [25,[27][28][29][30][31]. A type III CRISPR system has also been used to engineer phages that infect Staphylococcus aureus and Staphylococcus epidermidis [32].…”
Section: Introductionmentioning
confidence: 99%
“…Methods for genetically engineering phages have recently been reviewed (Pires et al 2016) and commonly involve homologous recombination and recombineering. While such approaches can be improved by clever incorporation of CRISPR-Cas systems (Kiro et al 2014, Lemay et al 2017, Schilling et al 2018, the overall modest efficiencies largely limits mutagenesis to the generation and single-site mutation of chimeric genomes Fane 2015, Doore et al 2017), gene deletions (Uchiyama et al 2009), and limited multi-site mutagenesis (Stockdale et al 2015). A recent approach combines mutagenesis by PCR with degenerate (NNK) primers with in-cell recombination to create variation at specific residues in the tail fiber of T3 phage (Yehl et al 2019).…”
Section: Introductionmentioning
confidence: 99%